The Dynamic Character as Seen in J.R.R Tolkien’s The Hobbit Novel - Mac Aditiawarman; Fitri Mardhatillah (Fakultas Sastra Universitas Ekasakti, 2018)
This research entitled “The Dynamic Character as seen in J.R.R Tolkien’s The Hobbit Novel”. about Thorin Oakenshield’s dynamic character, the king who wants to take back his kingdom. This research is limited on basic ideas that relate to the observation into three questions as follow: (1) Why does Thorin also has an important role (2) Why is Thorin not the true leader (3) Why does Thorin change his role from hero to villain. The purposes of the thesis are, (1) To analyze Thorin’s role in the Hobbit novel, (2) To analyze Thorin’s role as a leader who considered not the true leader, (3) To analyze Thorin Oakenshield’s dynamic character as the story progress. This theory using Teeuw and Pradopo about structural analysis and Griffith about dynamic character.As for data analysis method, the writer uses systematic procedures by understanding the novels, the characters, as well as the structural theory. Data collection technique uses documentation technique in finding relevant data to the subject of analysis. The results are: (1) Thorin who has important role in the Hobbit novel, (2) Thorin as the leader of the company but his quality as the leader is so bad, (3) The dynamic character of Thorin when he get back his kingdom.As conclusion, Tolkien shows that the crownless king has desire to get back his kingdom and becomes blind to the presence of the people around him. However, before his death he admits his wrongs to Bilbo. The moral value from this story is the world would be a better place if people cherished friendship and joy over wealth and success.